"Eating healthy": Distrust of expert nutritional knowledge among elderly adults. (1st October 2021) - Suarez, Maka; Torres Carrasco, María Elissa; Morales, Diana; Kuritzky, Amy; Abril, Victoria; Encalada, Lorena
Abstract: Elderly adults in southern Ecuador often distrust nutritionists' advice when implementing changes to their dietary practices. This distrust is no overt disregard for expert nutritional knowledge but rather the result of structural and situated practices that combine suspicion, misinformation, financial limitations, and family care. In this article, we examine eating practices among elderly adults in southern Ecuador in order to understand how nutrition distrust is constructed. In doing so, our aim is to understand how elderly adults incorporate—or not—expert nutritional knowledge into their eating practices. By ethnographically documenting daily eating practices among elderly adults in their homes, alongside expert nutritional discourses, our findings reveal that there is first, a local understanding of "eating healthy" connected to lived realities (e.g. farming practices, agricultural toxicity, age, education, polypharmacy, kinship ties), and second, a disconnect between expert nutritional knowledge and eating practices linked to how knowledge is produced and disseminated (e.g. power relations, scientific vocabulary, perceptions of health). Understanding how elderly adults build trust around eating can be a fertile ground for promoting more effective and suitable dietary advice among specific communities or groups like elderly adults.